Piroplasmid Infections Among Domestic Dogs in the Mountain City of Rio de Janeiro, Brazil - Palmer, João Pedro Siqueira; Gazêta, Gilberto Salles; André, Marcos Rogério [UNESP]; Fialho, Priscila Alves; Corrêa, Laís Lisboa; Damasceno, José André Lessa; Israel, Carolina Bistritschan; Pereira, Rafael Rempto; da Silva Barbosa, Alynne (Springer Nature, 2024)
Purpose: The aim of the present study was to analyze the frequency of the piroplasmids in blood from dogs and ticks recovered from these animals in Teresópolis city, located in the mountain region of Rio de Janeiro state, Brazil. In addition to the clinical and hematological profile. Methods: A total of 400 dogs attended in a veterinary clinic in this city between 2020 and 2021 were included. The blood was collected from the dogs, along with ticks and information on these dogs was obtained through a questionnaire applied to the owners. Thin-smear analyses and complete blood counts were performed. All forms characteristic of piroplasmids were measured and classified morphologically. The blood was also subjected to PCR assays based on the genes 18S rRNA and hsp70. In addition, the ixodid ticks were classified morphologically and subjected to PCR for piroplasmids research. The amplified products were sent for gene sequencing. Results: Piroplasmids were detected in 2.3% of the dogs. The variables statistically associated with infections in these animals were hemorrhage/bleeding, jaundice, anisocytosis, activated monocytes and macroplatelets (p ≤ 0.05). Piriform, ring-shaped, oval and aberrant structures were viewed in erythrocytes, neutrophils and monocytes, with lengths greater than and less than 2.5 µm. The nine positive samples from these dogs were characterized as due to Rangelia vitalii. However, one sequence from B. vogeli was detected in a single adult specimen of R. sanguineus. Conclusion: Although circulation of two species of piroplasmids potentially infective for domestic dogs has been observed in the mountain city of Rio de Janeiro, infection due to R. vitalii was mostly seen in the dogs of the present study.
Keywords: Babesia vogeli; Molecular diagnosis; Rangelia vitalii; Rio de Janeiro